1987
DOI: 10.1002/abio.370070602
|View full text |Cite
|
Sign up to set email alerts
|

Microbial recycling of mineral waste products

Abstract: The applicability of biotechnological methods to metal recovery from non‐sulfide industrial waste products (slag, galvanic sludge, filter‐press residue, filter dust, and fly ash) was investigated. From some products, copper, chromium, zinc or vanadium were completely extracted by sulfuric acid produced by Thiobacillus thiooxidans. The efficiency of bacterial metal solubilization varied depending on the type of waste material and on the pulp density. Stepwise increase of pulp density promoted bacterial growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
(1 reference statement)
0
11
0
3
Order By: Relevance
“…It is shown that percentages of copper, lead and zinc solubilized decrease with increase of concentration of PWBs in the both cases of 1.0-3.0 and 0.5-1.0 mm of sieve fraction. Especially, when the concentration of PWBs decreases from 7.8 to 19.5 g l −1 , percentages of copper, lead and zinc solubilized decreased considerably for most of the experimental cases, which illustrates that the concentration of PWBs should be controlled under a reasonable range although A. ferrooxidans was reported to be able to tolerate high metal concentrations [34,35].…”
Section: Resultsmentioning
confidence: 97%
“…It is shown that percentages of copper, lead and zinc solubilized decrease with increase of concentration of PWBs in the both cases of 1.0-3.0 and 0.5-1.0 mm of sieve fraction. Especially, when the concentration of PWBs decreases from 7.8 to 19.5 g l −1 , percentages of copper, lead and zinc solubilized decreased considerably for most of the experimental cases, which illustrates that the concentration of PWBs should be controlled under a reasonable range although A. ferrooxidans was reported to be able to tolerate high metal concentrations [34,35].…”
Section: Resultsmentioning
confidence: 97%
“…Metals may be amenable to microbial treatment in a number of ways, for example the oxidation of metal sulphides and sulphide containing ore by Thiobacillus ferroxidans is well documented and is commercially operated in the recovery of copper from low grade ores (84). The process has also been applied at a laboratory scale to a variety of other metals including cadmium, copper, nickel and zinc (85,86). The possibility of applying this technology to the treatment of metal contaminated soils has been suggested but does not appear to have been applied to date.…”
Section: Metalsmentioning
confidence: 99%
“…Experiments have shown that the metal oxides in such residues can be leached by acid produced by T. thiooxidans . Depending on the metal compounds in the residues, vanadium, chromium, copper and zinc can be almost completely recovered [58]. In some cases, chemical leaching is easier.…”
Section: Future Aspectsmentioning
confidence: 99%